1980
DOI: 10.1073/pnas.77.7.4221
|View full text |Cite
|
Sign up to set email alerts
|

Search for mutations affecting protein structure in children of atomic bomb survivors: preliminary report.

Abstract: A total of 289,868 locus tests, based on 28 different protein phenotypes and using one-dimensional electrophoresis to detect variant proteins, has yielded one probable mutation in the offspring of "proximally exposed" parents, who received an estimated average gonadal exposure of 31 to 39 rem in the atomic bombings of Hiroshima and Nagak. There were no mutations in 208,196 locus tests involving children of "distally exposed" parents, who had essentially no radiation exposure. Studies of the genetic effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
1

Year Published

1981
1981
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(65 citation statements)
references
References 19 publications
3
61
1
Order By: Relevance
“…The latest mortality study (Izumi et al, 2003) suggested that such exposure did not lead to increased cancer mortality rates in childhood and young adulthood among the offspring born in Hiroshima and Nagasaki. This finding is consistent with earlier studies of the cohort, which found no dose-dependent increases in mortality (Kato et al, 1966;Neel et al, 1974;Yoshimoto et al, 1991;Little et al, 1994), childhood cancer (Yoshimoto et al, 1990), untoward pregnancy outcomes (Neel and Schull, 1956;Otake et al, 1990), cytogenetic abnormalities (Awa et al, 1987), or loss of enzyme activity (Neel et al, 1988). However, because cancers with high survival rates could not be adequately evaluated by mortality data, the effects of parental irradiation on cancer risks among the offspring need to be examined using the cancer incidence data.…”
supporting
confidence: 89%
“…The latest mortality study (Izumi et al, 2003) suggested that such exposure did not lead to increased cancer mortality rates in childhood and young adulthood among the offspring born in Hiroshima and Nagasaki. This finding is consistent with earlier studies of the cohort, which found no dose-dependent increases in mortality (Kato et al, 1966;Neel et al, 1974;Yoshimoto et al, 1991;Little et al, 1994), childhood cancer (Yoshimoto et al, 1990), untoward pregnancy outcomes (Neel and Schull, 1956;Otake et al, 1990), cytogenetic abnormalities (Awa et al, 1987), or loss of enzyme activity (Neel et al, 1988). However, because cancers with high survival rates could not be adequately evaluated by mortality data, the effects of parental irradiation on cancer risks among the offspring need to be examined using the cancer incidence data.…”
supporting
confidence: 89%
“…Further, analyses of mutations in microsatellite DNA obtained from children born to atomic bomb survivors has demonstrated similar mutant frequencies among these children and children born to nonexposed parents [40,41]. An analysis of proteins by starch gel electrophoresis also found similar levels of mutation in offspring of atomic bomb survivors and children born to control parents [42].…”
Section: Discussionmentioning
confidence: 95%
“…As the purpose differed between the two studies, the method of the family study also differed in the two populations. For the Adult population, family study was pursued until a variant identical to that of the propositus was encountered , while in the case of the Child population, the purpose was specifically to examine parents (Neel et aL, 1980). In either population, while some families were cooperative, others were not or family members did not reside in Hiroshima or Nagasaki.…”
Section: Samples and Family Studiesmentioning
confidence: 99%
“…After a pilot study of A-bomb survivors, an electrophoretic study of children of survivors was undertaken, and interim reports were published (Neel et al, 1980;Satoh et al, 1982aSatoh et al, , 1982b. By the end of September 1982, a total of 11,534 children of proximally exposed parents and 9,092 children of distally exposed parents were examined for variants in a maximum of 30 protein systems, the number of systems examined differing from child to child.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation